2007
DOI: 10.1111/j.1440-1584.2007.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Securing and retaining a mental health workforce in Far Western New South Wales

Abstract: Strategies to recruit and retain staff must take account of personal needs and aspirations. While there is room for state strategies to improve employment incentives, there is also considerable scope for local managers to improve the design and attractiveness of jobs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 7 publications
1
58
0
Order By: Relevance
“…It is possible that offering career advancement opportunities leads workers to either advance in their own agencies or seek employment at other agencies that provide better opportunities. One study conducted outside of the U.S. reported that many mental health workers leave to seek better career opportunities (Perkins et al 2007). If agencies would like to retain workers while encouraging career advancement, they could broaden advancement opportunities to include career lattices within existing CPST positions and ensure that advancement is not limited to managerial-level positions.…”
Section: Career Advancement Opportunitiesmentioning
confidence: 98%
See 1 more Smart Citation
“…It is possible that offering career advancement opportunities leads workers to either advance in their own agencies or seek employment at other agencies that provide better opportunities. One study conducted outside of the U.S. reported that many mental health workers leave to seek better career opportunities (Perkins et al 2007). If agencies would like to retain workers while encouraging career advancement, they could broaden advancement opportunities to include career lattices within existing CPST positions and ensure that advancement is not limited to managerial-level positions.…”
Section: Career Advancement Opportunitiesmentioning
confidence: 98%
“…Turnover, i.e., leaving one's position, has been linked to a variety of factors including a desire for better career opportunities, low pay, inadequate skills/training, inadequate benefits, and a lack of workplace supports (Baraket al 2001;Ben-Dror 1994;Jayaratne and Chess 1984;Perkins et al 2007). Currently, annual turnover rates for mental health workers are estimated at 30 % (Garner et al 2012;Gitter 2009;Rollins et al 2010).…”
Section: Introduction Turnover Among Community Mental Health Workers mentioning
confidence: 99%
“…It has also been noted that existing attachments within the community, such as friends or family members, promote greater satisfaction with rural lifestyle (Perkins et al, 2007). At the same time, such attachments increase the challenges of dual relationships and personal-professional boundaries (Gillespie and Redivo, 2012).…”
Section: Factors Impacting the Satisfaction Of Rural Mental Health Prmentioning
confidence: 98%
“…It is indeed plausible that the addition of a scholarship recipient to an area where few physicians practice will make the area more attractive for colleagues. Some of the reasons that physicians cite for their intention to leave an underserved area—heavy workloads (Charles, Ward, and Lopez 2005; Perkins et al 2007; Richards, Farmer, and Selvaraj 2005; WHO 2004), lack of contact with colleagues (Richards et al 2005; Stilwell et al 2004), lack of support from medical specialists (Kotzee and Couper 2006), and social isolation—would presumably decrease in strength if more physicians worked there (Charles et al 2005). …”
Section: The Effectiveness Of Conditional Scholarshipsmentioning
confidence: 99%